The Silent Shunt: Traumatic Splenic AV Fistula Revealed and Treated Endovascularly - Sharma, Gulshan; Singh, Resham; Garg, Puneet (Acta medica Lituanica, 2025)
Background: Splenic arteriovenous fistula (AVF) is a rare vascular anomaly that can arise from trauma, aneurysmal rupture, or congenital conditions. Prompt diagnosis and management are crucial to preventing complications such as portal hypertension and high-output cardiac failure.Case Presentation: We present the case of a 62-year-old male with a traumatic splenic AVF resulting from a road traffic accident (RTA), associated with a Grade IV splenic injury and multiple pseudoaneurysms. The patient underwent successful endovascular coil embolization and experienced an asymptomatic follow-up.Conclusion: Endovascular coil embolisation is a minimally invasive and effective first-line treatment for traumatic splenic AVFs, particularly in hemodynamically stable patients, providing excellent outcomes and organ preservation.
Keywords: arteriovenous fistula; spleen; trauma; endovascular